2019
DOI: 10.3390/ijerph16050694
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate Change and Heterogeneity of Local Climates on the Development of Malaria Parasite (Plasmodium vivax) in Moscow Megacity Region

Abstract: The article presents the results of a spatio-temporal analysis of the changes of the favorability of climatic conditions for the transmission of vivax malaria in the Moscow megacity and its surroundings during the period from 1977 to 2016. Using the historical temperature records at urban and rural weather stations, we calculated the key indicators of climate favorability for malaria transmission, viz. the sum of effective temperatures, the duration of the season of effective infectiveness, and a new integral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…• T • C (14 • C) is the lowest temperature threshold below which Dirofilaria development within a mosquito vector does not occur; • 130 degrees/days is "a sum of effective temperatures" (SET) or "growing degree day" (adopted in several models in the West) needed for Dirofilaria larvae to reach infectivity. The concept of SET was originally developed and successfully applied in Russia in the control of malaria [65]. This approach was applied to other vector-borne diseases as well, for example, for cutaneous leishmaniasis [66].…”
Section: Control and Prevention Of Dirofilariasis In The Russian Fedementioning
confidence: 99%
“…• T • C (14 • C) is the lowest temperature threshold below which Dirofilaria development within a mosquito vector does not occur; • 130 degrees/days is "a sum of effective temperatures" (SET) or "growing degree day" (adopted in several models in the West) needed for Dirofilaria larvae to reach infectivity. The concept of SET was originally developed and successfully applied in Russia in the control of malaria [65]. This approach was applied to other vector-borne diseases as well, for example, for cutaneous leishmaniasis [66].…”
Section: Control and Prevention Of Dirofilariasis In The Russian Fedementioning
confidence: 99%
“…An outbreak of vivax malaria in Moscow region has developed amid exceptionally favourable weather conditions for the vivax pathogen's extrinsic development. It was previously demonstrated that by the start of the 21st Century, conditions for malaria transmission in Moscow region improved compared with 1970-80s [51]. The most dramatic changes in the sums of effective temperatures and duration of season of effective mosquito infectivity have occurred since the mid-1990s, which is consistent with general climatic warming in Moscow region [27].…”
Section: Discussionmentioning
confidence: 68%
“…For the purpose of malaria, the method has been recommended by the WHO [50,51]. According to Moshkovsky, extrinsic development of P. vivax requires the accumulated sum of 105 degree-days above the threshold of 14.5 ℃.…”
Section: Climate Favourability Assessmentmentioning
confidence: 99%
“…Sophisticated spatial interpolation is needed to satisfy the interests of stakeholders (Taheri-Shahraiyni and Sodoudi 2017; Beck et al 2018). This complication is rather unfortunate because the lack of knowledge about local temperature variations might impede identification of ecosystem refugia (e.g., Gregg et al 2003;Dobrowski 2011;Miles and Esau 2016;Bois et al 2018) as well as of environmental and health risks (e.g., Buscail et al 2012;Hjort et al 2016;Varentsov et al 2018;Mironova et al 2019). Detailed temperature maps are also required to optimize urban green space and urban comfort (e.g., Fernández et al 2015;Zhang et al 2017) and, more broadly, to improve urban management (e.g., Shao et al 1997;Szymanowski and Kryza 2009;Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 99%